If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -2 = 2y + -20 Reorder the terms: -2 + 7y = 2y + -20 Reorder the terms: -2 + 7y = -20 + 2y Solving -2 + 7y = -20 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -2 + 7y + -2y = -20 + 2y + -2y Combine like terms: 7y + -2y = 5y -2 + 5y = -20 + 2y + -2y Combine like terms: 2y + -2y = 0 -2 + 5y = -20 + 0 -2 + 5y = -20 Add '2' to each side of the equation. -2 + 2 + 5y = -20 + 2 Combine like terms: -2 + 2 = 0 0 + 5y = -20 + 2 5y = -20 + 2 Combine like terms: -20 + 2 = -18 5y = -18 Divide each side by '5'. y = -3.6 Simplifying y = -3.6
| -5+7v=6(6v+4) | | 0=2x+3x | | 3(2x-8)-5(15-6x)=9(4x-11) | | 10x+22=-2(x+5) | | 61=-9(v-9)+3(-6+3v) | | 8(k+8)=3k+29 | | 6k+6k=12 | | 5d+54=89 | | 7-7(n+5)=-24-8n | | -7n-5=-5(n-1) | | 9r-5r-6r= | | -3x-1x=-12 | | 3x-12=2(5x-10) | | 14+x=6-x | | -6v-30=-6(1+2v) | | -6-8=n | | x+(x+120)+2x=660 | | 2y=2(y-3) | | 13x+6=(x+6) | | 11(3x-2)+12=-10(1+10x) | | x-4(1+2x)=-8x-10 | | 5=-1+2k+4k | | 8-14=n | | 11x+6=2x+24 | | 6y-10=6y+10 | | 7z+7-3z=10+3z+7 | | -24+8n=8(n-6)-6n | | 9-10n=-81 | | 4(4-w)=2(-5+4y) | | -5-8a=8-7(a+2) | | 40=8(-1-7x)+4(-3x-5) | | 3x-8=6x-4 |